Efeito da inoculação da levedura rizosférica Torulaspora globosa (6S01) em combinação com glicose e triptofano, sobre o desenvolvimento inicial de milho - Corrêa, Patrícia Herrmann (2019)
Plant Growth Promoter Microorganisms (PGPMs) stimulate the development of plants by different mechanisms, such as the production of plant hormones and solubilization of minerals. The species Torulaspora globosa, isolated from the rhizosphere of sugar cane and maize, proved effective for the production of indoleacetic acid and organic acids capable of solubilizing minerals, such as phosphate, with potential to stimulate plant growth. The objective of this work was to evaluate the effect of T. globosa yeast (6S01 strain) and addition of glucose and/or tryptophan in the initial development of corn under controlled conditions.Sixteen treatments were evaluated, with 106 and 103 cells/mL being evaluated at different times, each inoculating in seed and/or plant, and adding glucose and/or tryptophan, with six replicates per treatment. The experimental design was a completely randomized design. The concentration of glucose (20 g/mL) and the concentration of tryptophan (0.1%). The evaluation was carried out by the parameters of shoot length and root and dry mass of shoot and root. It was observed that the addition of glucose in the yeast inoculation treatments promoted the damage in the initial development of the plant of both concentrations. Tryptophan favored the increase of the root dry mass, inoculation of the seed and plant or the seed in the lowest concentration of cells and the concentration of 106 cells / mL when inoculating the seed. The inoculum at the concentration of 106 cells / mL gave better results, but was statistically similar to the control, except for the evaluation of the aerial part of the corn in the treatments of seed and plant inoculation and the dry mass of the aerial part, also without statistical difference with the control. This is an unprecedented but preliminary study, since it was carried out under controlled conditions, and only with analysis of the initial development of the corn plant. The results obtained are promising and motivate further studies, with the use of inoculation of the plants in non-sterile soil, greenhouse and in the field.